Comparative application of biological and ninhydrin- derivatized spectrophotometric assays in the evaluation and validation of amikacin sulfate injection - Edebi Nicholas Vaikosen; Samuel Ogheneruona Origbo; Diepreye Ere; Prosper Odaderia (Universidade de São Paulo, 2023)
Abstract Instrumental techniques are preferred over bioassay methods for antibiotic quantification mainly due to speed and ability to quantify metabolites in biological samples; however, the potency and biological activity of these drugs cannot be assessed. Two methods - agar well diffusion (bio-assay) and spectrophotometric methods were used to evaluate amikacin sulfate injection. Agar plates were inoculated with S. aureus inoculum; zones of inhibition from its susceptibility to amikacin were obtained, while spectrophotometric absorption at 650 nm of ninhydrin- derivatized amikacin in phosphate buffer (pH 8) was measured. Methods performance showed linearity from 1 - 16 μgmL-1 (bioassay, r = 0.9994) and 10-50 μgmL-1 (spectrophotometric, r = 0.9998). Molar absorptivity was 2.595 x 104 Lmol-1cm-1. Limits of detection and quantification were 1.07 and 3.24 μgmL-1 respectively for bioassay method, while corresponding values for spectrophotometric method were 0.98 and 2.97 μg mL-1. Relative standard deviations were ≤ 2.0% for both methods, with recoveries from 95.93 - 100.25%. Amikacin in brands ranged from 97.53 ± 2.68 to 100.84 ± 1.82%, student's t-test was ≤ 2.78 (n = 4) with respect to label claim for both methods. Experimental paired t-test (t = 2.07; n = 4) and F-test (F = 3.94; n = 4) values indicated no significant difference between both methods, hence comparable and can jointly be used in quality control assessment of antibiotics.